2017
DOI: 10.22323/2.16030206
|View full text |Cite
|
Sign up to set email alerts
|

Beyond propaganda: science coverage in Soviet Estonian media

Abstract: Previous studies have concluded that science coverage in Soviet countries was determined by the ideological function of the media. This paper analyses the science coverage in Soviet Estonian publications Rahva Hääl and Horisont in 1960/1967 and 1980 and demonstrates that the popularization of science existed as an independent function of articles. This suggests that the parallel developments in science communication on both sides of the Iron Curtain deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The research studies carried out so far (Joubert, 2018; Manzini, 2003; Massarani, 2014; Olesk, 2017) confirm the interconnection between science and science communication, on the one hand, and specific socio-historical, political and economic contexts, on the other hand. Ukrainian science has acutely felt it on itself.…”
Section: Introduction: Ukraine’s Science Communication’s Rootsmentioning
confidence: 54%
See 2 more Smart Citations
“…The research studies carried out so far (Joubert, 2018; Manzini, 2003; Massarani, 2014; Olesk, 2017) confirm the interconnection between science and science communication, on the one hand, and specific socio-historical, political and economic contexts, on the other hand. Ukrainian science has acutely felt it on itself.…”
Section: Introduction: Ukraine’s Science Communication’s Rootsmentioning
confidence: 54%
“…Kellner and Share (2007, p. 59) argue that ‘critical media literacy is crucial for participatory democracy in the twenty-first century’. Today, according to Olesk (2017), contributing a critical understanding of science is considered as the core of good science communication, including one of the main tasks of science journalism.…”
Section: Discussion: What To Pay Attention To In Order To Improve Medmentioning
confidence: 99%
See 1 more Smart Citation
“…The magazine offered articles written by Estonian scientists in an accessible language and sometimes provided adaptions from Western popular science magazines. During the first years, the topics mostly covered global science and the latest scientific advances, while later coverage became more timeless and focused on local and Soviet topics (Olesk, 2017). The magazine enjoyed its greatest popularity in the 1970s with a top circulation of 54,000 in 1971.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…As a result, we can distinguish two types of public science communication: one whose aim was not to introduce or explain science but to use science examples or scientists to reinforce ideological discourses such as legitimisation of the Soviet system; and the other that sought to popularise and explain science. A study on the science coverage in Soviet Estonian media (Olesk, 2017) showed that although the first type was predominant, the second type was also present, especially in Horisont, but also in daily newspapers, probably more due to the personal initiative of some scientists and journalists than to editorial policy.…”
Section: Historical Backgroundmentioning
confidence: 99%